The Relation of The Urban Settlement Quality Improvement Program and Land Prices: Case Study DKI Jakarta - Rizka Amalia; Khoirunurrofik Khoirunurrofik (Journal Research of Social Science, Economics, and Management, 2025)
The Urban Settlement Quality Improvement Program was implemented in 220 slum areas (RW) in DKI Jakarta between 2018 and 2022, focusing on physical and non-physical aspects of urban quality. This study measures the impact of this program on land prices within these areas. Using the Staggered Difference in Differences (DiD) method, it was found that land price increases in developed areas showed weak statistical significance, with an average rise of Rp 68,919 per square meter compared to control areas. These findings suggest that the program’s primary objective was enhancing quality of life rather than directly influencing land values. These insights are essential for designing more integrated urban policies in rapidly urbanizing cities like Jakarta.